2016
DOI: 10.1161/circimaging.115.004330
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Machine-Learning Algorithm for Cardiac Imaging

Abstract: Background Associating a patient’s profile with the memories of prototypical patients built through previous repeat clinical experience is a key process in clinical judgment. We hypothesized that a similar process using a cognitive computing tool would be well suited for learning and recalling multidimensional attributes of speckle tracking echocardiography (STE) data sets derived from patients with known constrictive pericarditis (CP) and restrictive cardiomyopathy (RCM). Methods and Results Clinical and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(73 citation statements)
references
References 30 publications
1
68
0
4
Order By: Relevance
“…In a recent study, we have created temporal models of disease trajectories that could potentially reveal how the population could cluster into subgroups based on age, gender, self-reported ancestry and comorbidities 34 . Further, we have shown that cognitive machine learning can be utilized for precise phenotyping of high volume echocardiography datasets 35 . We have also applied machine learning to understand various features driving patient satisfaction 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we have created temporal models of disease trajectories that could potentially reveal how the population could cluster into subgroups based on age, gender, self-reported ancestry and comorbidities 34 . Further, we have shown that cognitive machine learning can be utilized for precise phenotyping of high volume echocardiography datasets 35 . We have also applied machine learning to understand various features driving patient satisfaction 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Ortiz et al 30 used neural networks to analyze cardiac contractility to predict 1-year mortality in patients with heart failure. Since this early work, supervised machine learning 26 RV, LV endocardium and epicardium CNN Tan et al 27 LV segmentation ANN Baessler et al 28 Myocardial scar detection Random forests Dawes et al 29 Pulmonary hypertension prognosis PCA ECHO Ortiz et al 30 HF prognosis ANN Narula et al 31 HCM vs athlete's heart SVM, Random forests, ANN Sengupta et al 32 Constrictive pericarditis vs restrictive cardiomyopathy AMC, random forest, k-NN, SVM Sengur 33 Valvular disease SVM Moghaddasi and Nourian 34 MR severity SVM Vidya et al 35 MI detection SVM CT Wolterink et al 36 CAC scoring CNN Isgum et al 37 CAC scoring k-NN, SVM Itu et al 38 FFR estimation deep neural network Motwani et al 39 Prognosis Logistic regression Mannil et al 40 MI detection Decision tree, k-NN, random forest, ANN 32 diagnose valvular heart disease, 33 grade severity of mitral valve regurgitation, 34 automate ejection fraction measurement, 53 and detect the presence of myocardial infarction. 35,54 Several machine learning applications have also been developed to assist in the interpretation of CT. For example, algorithms have been developed for the automation of coronary artery calcium scoring 36,37,55,56 and assessment of the functional significance of coronary lesions.…”
Section: Applications To Cardiovascular Diseasementioning
confidence: 99%
“…Murata and others as stated in [7] studied the machine learning and various textual features in language use process. In addition, the machine learning algorithm that is proposed by Sengupta and others as stated in [8] are fully considered. The further development of machine learning algorithm has changed the traditional way of research in the field of Natural Language Processing.…”
Section: Literature Reviewmentioning
confidence: 99%